(untitled) (MAUSAM, 2025)
An attempt has been made in the present paper to examine the usefulness of Outgoing Longwave Radiation (OLR) over Southern Hemispheric Equatorial Trough (SHET) in foreshadowing Indian Summer Monsoon Rainfall (ISMR) qualitatively during extreme ISMR (deficient or excess) years. The daily OLR data analyzed in the study are computed on weekly basis over June- September for the study of lagged correlation between the SHET and ISMR. For developing a model for Long Range Forecasting of ISMR and its verification OLR data for a period of 30 years (1981-2010) have been used.However, SHET is not always active across its entire zone of 40°E to 100° E. To compare the relative role of SHET activity in its western and eastern parts on the variability of rainfall over India as a whole, the SHET zone has been divided into three parts: Western SHET (WSHET) (-5° to -15°S, 40°-60°E), Central SHET (CSHET) (-5° to -15°S, 60°-80°E) and Eastern SHET (ESHET) (-5° to -15°S, 80°-100°E). The mean OLR was computed by averaging throughout the WSHET, CSHET, and ESHET regions for 20 weeks of the season every 30 years (1981-2010). In the current study, WSHET and CSHET had a good negative correlation (-0.52 and -0.55) with AISMR. The significant features of SHET in three excess years (1983, 1988 and 1994) show that there is marked difference in the spatial and temporal variability OLR in monthly as well as seasonal scale. During deficient monsoon years (1982, 2002 and 2009), it was observed that convection was more than normal over Pacific region as well as over southern equatorial Indian Ocean. During deficient years, Eastern Equatorial Indian Ocean SHET (ESHET) OLR was significantly negatively correlated with AISMR whereas there is no significant correlation with Western Equatorial Indian Ocean SHET (WSHET) OLR.